Prevalence of Emergence Delirium in Children Undergoing Tonsillectomy and Adenoidectomy - Katie Liu; Christopher Liu; Seckin O. Ulualp (Anesthesiology Research and Practice)
Objective. Emergence delirium (ED) is associated with behavioral disturbances and psychomotor agitation, increased risk of selfinjury, delayed discharge, and parental dissatisfaction with quality of care. Otolaryngology procedures are associated with an increased risk of ED. The aims of this study were to determine the prevalence of ED in children who had tonsillectomy and adenoidectomy (T&A), assess the characteristics of children who had ED, and ascertain the recovery times of patients with ED. Methods. Charts of patients who had tonsillectomy and adenoidectomy between Jan 1, 2018 and March 26, 2020 at a tertiary children’s hospital were reviewed. Data collection included demographics, body mass index, indication for T&A, Pediatric Anesthesia Emergence Delirium (PAED) score, American Society of Anesthesiologists (ASA) physical status classification, total anesthesia time, postanesthesia care phase I time, and postanesthesia care phase II time. Results. Of the 4974 patients who underwent T&A, ED occurred in 1.3% of patients. Toddlers (2.9%) and male children (1.6%) had a significantly higher prevalence of ED. Prevalence of ED was similar amongst patients with recurrent tonsillitis, patients with obstructive sleep disordered breathing, and patients with both obstructive sleep apnea (OSA) and recurrent tonsillitis. The prevalence of ED was not different amongst ASA I, ASA II, and ASA III. Males with ED had longer total anesthesia times (41 v. 34 minutes, p=0.02) and ASA I patients with ED had longer phase I times (p=0.04) in the postanesthesia care unit (PACU). There was no significant difference in total anesthesia time, phase I time, or phase II time when compared across the subgroups of gender, age, indication for T&A, severity of obstructive sleep apnea (OSA), and ASA score. Conclusions. Males, toddlers, and preschool-age children were more likely to have ED. Males with ED had longer total anesthesia times. ED was associated with longer phase I times in ASA I patients.